The reliability evaluation research of distribution system considering demand response - Na Li; Xiaoliang Wang; Zhenhua Zhu; Yanan Wang (Energy Reports, 2020)
In order to evaluate the reliability of distribution system with demand response, this paper established the load peak-valley partition model and demand response model corresponding to every period based on load peak-valley characteristics. Then considering the characteristics of distribution system, the reliability evaluation model considering demand response was established. The example simulation verified that the demand response participated in load reduction strategy could effectively improve the reliability level of the distribution system.
Keywords: 330; Demand response; Distribution system; Reliability evaluation